Microsoft Office Excel 2007 - Frye, Curtis, 1968- (Step by step (Redmond, Wash.), 2007)
Experience learning made easy—and quickly teach yourself how to organize, analyze, and present data with Excel 2007. With Step By Step, you set the pace—building and practicing the skills you need, just when you need them!Create formulas, calculate values, and analyze dataPresent information visually with graphics, charts, and diagramsBuild PivotTable dynamic views—even easier with new data tablesReuse information from databases and other documentsShare spreadsheets for review and manage changesCreate macros to automate repetitive tasks and simplify your workYour all-in-one learning experience includes:Files for building skills and practicing the book’s lessonsFully searchable eBookBonus quick reference to the Ribbon, the new Microsoft Office interfaceWindows Vista® Product Guide eReference—plus other resources on CDA Note Regarding the CD or DVDThe print version of this book ships with a CD or DVD. For those customers purchasing one of the digital formats in which this book is available, we are pleased to offer the CD/DVD content as a free download via OReilly Medias Digital Distribution services. To download this content, please visit OReillys web site, search for the title of this book to find its catalog page, and click on the link below the cover image (Examples, Companion Content, or Practice Files). Note that while we provide as much of the media content as we are able via free download, we are sometimes limited by licensing restrictions. Please direct any questions or concerns to booktech@oreilly.com.